The place where poetries meet: exploring the contribution of the InZync poetry sessions to sociocultural transformation in Stellenbosch - Odendaal, Petrus Johannes Loock (Stellenbosch : Stellenbosch University, 2017)
Thesis (MPA)--Stellenbosch University, 2017.